2013
DOI: 10.1111/j.1532-950x.2013.12030.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics and Local Tolerance at Injection Site of Marbofloxacin Administered by Regional Intravenous Limb Perfusion in Standing Horses

Abstract: These data suggest that RIVLP of marbofloxacin (0.67 mg/kg) could be a safe and effective method for treatment of infections of the distal portion of the limb for susceptible organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Pharmacodynamic studies have shown that all three indices, T>MIC (time the concentration remains above the MIC), C max and area under the curve, are important in evaluating antimicrobial efficacy, and even β-lactams efficacy can gain from higher C max (Gunderson and others 2001). RLP PK studies in horses support the use of ceftiofur, vancomycin, erythromycin, enrofloxacin, marbofloxacin and chloramphenicol (Pille and others 2005, Rubio-Martínez and others 2005, Parra-Sanchez and others 2006, Kelmer and others 2013b, 2015, Lallemand and others 2013). Meticillin-resistant Staphylococcus aureus (MRSA) infections are becoming more common in equine medicine and due to their MDR nature they pose a therapeutic challenge (Weese and others 2005).…”
Section: Antimicrobial To Usementioning
confidence: 95%
“…Pharmacodynamic studies have shown that all three indices, T>MIC (time the concentration remains above the MIC), C max and area under the curve, are important in evaluating antimicrobial efficacy, and even β-lactams efficacy can gain from higher C max (Gunderson and others 2001). RLP PK studies in horses support the use of ceftiofur, vancomycin, erythromycin, enrofloxacin, marbofloxacin and chloramphenicol (Pille and others 2005, Rubio-Martínez and others 2005, Parra-Sanchez and others 2006, Kelmer and others 2013b, 2015, Lallemand and others 2013). Meticillin-resistant Staphylococcus aureus (MRSA) infections are becoming more common in equine medicine and due to their MDR nature they pose a therapeutic challenge (Weese and others 2005).…”
Section: Antimicrobial To Usementioning
confidence: 95%
“…IVRLP achieves high concentration and pressure gradients by use of a tourniquet and increased vascular volume . The pharmacokinetic parameters of IVRLP have been investigated in the horse for amikacin, gentamicin, chloramphenicol, erythromycin, enrofloxacin, imipenem, vancomycin, marbofloxacin, and ceftiofur . IVRLP produces high concentrations of antimicrobial in the synovial fluid and tissues of the entire isolated portion of the limb .…”
Section: Introductionmentioning
confidence: 99%
“…18 The constant battle against resistant bacteria creates a growing need for the development of more efficient treatments. As a result, significant research effort has recently focused on RLP, such as investigating combinations of antimicrobials, 19,20 the use of additional types of antimicrobials, [21][22][23][24] and improving the technique. 9,11,25 Ceftazidime is a member of the third generation cephalosporin group of b-lactam antibiotics.…”
Section: Introductionmentioning
confidence: 99%